2018
DOI: 10.2147/copd.s148685
|View full text |Cite
|
Sign up to set email alerts
|

Narrative medicine to improve the management and quality of life of patients with COPD: the first experience applying parallel chart in Italy

Abstract: PurposePoor adherence to therapy and the failure of current smoking cessation programs demonstrate that the current management of COPD can be improved, and it is necessary to educate physicians about new approaches for taking care of patients. Parallel chart is a narrative medicine tool that improves the doctor–patient relationship by asking physicians to write about their patients’ lives, thereby encouraging reflective thoughts on care.Patients and methodsBetween October 2015 and March 2016, 50 Italian pulmon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
31
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
3
1

Relationship

2
6

Authors

Journals

citations
Cited by 29 publications
(32 citation statements)
references
References 37 publications
0
31
0
Order By: Relevance
“…The positive effect of narrative medicine on a patient's physical and mental health has been confirmed by previous studies. For example, the narrative medical intervention helped to improve the self-management and quality of life of COPD patients, 18 reduced the depressive emotion level in patients with Parkinson's disease, 19 reduced pain and improved well-being in cancer patients, 20 and reduced polypharmacy. 21…”
Section: Discussionmentioning
confidence: 99%
“…The positive effect of narrative medicine on a patient's physical and mental health has been confirmed by previous studies. For example, the narrative medical intervention helped to improve the self-management and quality of life of COPD patients, 18 reduced the depressive emotion level in patients with Parkinson's disease, 19 reduced pain and improved well-being in cancer patients, 20 and reduced polypharmacy. 21…”
Section: Discussionmentioning
confidence: 99%
“…The main tools of this methodology are parallel charts and illness plots, dedicated to healthcare professionals and patients-caregivers, respectively [14,15]. Recent studies have demonstrated advantages of applying the parallel chart in exploring a healthcare professional's point of view about the pathway of care for chronic conditions (i.e., chronic obstructive pulmonary disease [COPD]) and doctor-patient relationships [16,17]. Similarly, patient and caregiver illness plots were recently shown to be a source of information on personal coping with the disease, and on how patients and their families rearrange their lives after a diagnosis in studies in other chronic diseases [18][19][20].…”
Section: Introductionmentioning
confidence: 99%
“…We read the article on the relationship between narrative medicine and the positive outcomes reflected in COPD management, by Banfi et al 1 with great interest. We were particularly intrigued by how the simple documentation of parallel charts could improve the patient–doctor relationship and patient adherence to treatment.…”
mentioning
confidence: 99%
“…The article 1 highlights that narrative medicine improves the patient–doctor relationship and hence patient outcomes. Graffigna et al 2 suggested a multidimensional association between the patient–doctor relationship, patient engagement, and medical adherence for patients with chronic conditions.…”
mentioning
confidence: 99%
See 1 more Smart Citation